Actions at a glance: The time course of action, object, and scene recognition in a free recall paradigm. - Reger, Maximilian; Vrabie, Oleg; Volberg, Gregor; Lingnau, Angelika (Cognitive, Affective & Behavioral Neuroscience, 2025)
Being able to quickly recognize other people's actions lies at the heart of our ability to efficiently interact with our environment. Action recognition has been suggested to rely on the analysis and integration of information from different perceptual subsystems, e.g., for the processing of objects and scenes. However, stimulus presentation times that are required to extract information about actions, objects, and scenes to our knowledge have not yet been directly compared. To address this gap in the literature, we compared the recognition thresholds for actions, objects, and scenes. First, 30 participants were presented with grayscale images depicting different actions at variable presentation times (33–500 ms) and provided written descriptions of each image. Next, ten naïve raters evaluated these descriptions with respect to the presence and accuracy of information related to actions, objects, scenes, and sensory information. Comparing thresholds across presentation times, we found that recognizing actions required shorter presentation times (from 60 ms onwards) than objects (68 ms) and scenes (84 ms). More specific actions required presentation times of approximately 100 ms. Moreover, thresholds were modulated by action category, with the lowest thresholds for locomotion and the highest thresholds for food-related actions. Together, our data suggest that perceptual evidence for actions, objects, and scenes is gathered in parallel when these are presented in the same scene but accumulates faster for actions that reflect static body posture recognition than for objects and scenes.